2001
DOI: 10.1038/sj.onc.1204397
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor protein VHL is induced at high cell density and mediates contact inhibition of cell growth

Abstract: In spite of the general recognition of von Hippel-Lindau (VHL) as a tumor suppressor gene, the physiological and pathological importance of VHL protein in cell growth regulation and tumorigenesis remains unclear. Here we show that in normal human renal proximal tubule epithelial cells (RPTEC), the steady-state amount of VHL protein is strictly regulated by cell density. The cellular VHL content is more than 100-fold higher in dense cultures than in sparse cultures. The increase in VHL protein at high cell dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…Consistent with our finding, Baba et al (2001) also showed that the expression of pVHL is cell densitydependent. They reported that VHL negative renal carcinoma cells continued to grow after attaining confluence and that VHL positive cells underwent cell cycle arrest.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with our finding, Baba et al (2001) also showed that the expression of pVHL is cell densitydependent. They reported that VHL negative renal carcinoma cells continued to grow after attaining confluence and that VHL positive cells underwent cell cycle arrest.…”
Section: Discussionsupporting
confidence: 81%
“…pVHL has been reported to have a number of biochemical functions, including regulation of microtubule stability, cell differentiation, cell motility, extracellular matrix assembly, JunB, and atypical isoforms of protein kinase C (15,(17)(18)(19)(20)(21)(22). However, the best characterized function of pVHL is to act as an essential component in the degradation of HIF-␣ subunits (10,14).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, VHL disease-associated pheochromocytoma has been speculated to develop as a result of a gain of function of pVHL, as this tumor type is almost exclusively observed in the setting of missense mutations (34). Furthermore, several activities have been ascribed to pVHL in addition to the regulation of the hypoxia response pathway and were recently reviewed (35), including potential function in cell cycle regulation (36 -38), cell growth (39,40), cytoskeletal structure (41,42), and extracellular matrix deposition (43). In this report we take advantage of genotype-phenotype correlation, and we have complemented Vhl Ϫ/Ϫ embryonic stem cells with a selected group of mutations representing the various subtypes of VHL disease, including Chuvash Polycythemia, to dissect potentially distinct activities of pVHL that are intrinsic to tissue-specific tumor types seen in the hereditary disease.…”
Section: Introductionmentioning
confidence: 99%